Risk of severe illness from COVID‐19 among Aboriginal and Torres Strait Islander adults: the construct of 'vulnerable populations' obscures the root causes of health inequities. (22nd September 2021) - Thurber, Katherine A.; Barrett, Eden M.; Agostino, Jason; Chamberlain, Catherine; Ward, James; Wade, Vicki; Belfrage, Mary; Maddox, Raglan; Peiris, David; Walker, Jennie; Baffour, Bernard; Wenitong, Mark; et al.
Abstract: Objective : To quantify the prevalence of known health‐related risk factors for severe COVID‐19 illness among Aboriginal and Torres Strait Islander adults, and their relationship with social determinants. Methods : Weighted cross‐sectional analysis of the 2018‐19 National Aboriginal and Torres Strait Islander Health Survey; Odds Ratios for cumulative risk count category (0, 1, or ≥2 health‐related risk factors) by social factors calculated using ordered logistic regression. Results : Of the adult population, 42.9%(95%CI:40.6, 45.2) had none of the examined health‐related risk factors; 38.9%(36.6, 41.1) had 1, and 18.2%(16.7, 19.7) had ≥2. Adults experiencing relative advantage across social indicators had significantly lower cumulative risk counts, with 30‐70% lower odds of being in a higher risk category. Conclusions : Aboriginal and Torres Strait Islander peoples must continue to be recognised as a priority population in all stages of pandemic preparedness and response as they have disproportionate exposure to social factors associated with risk of severe COVID‐19 illness. Indigeneity itself is not a 'risk' factor and must be viewed in the wider context of inequities that impact health Implications for public health : Multi‐sectoral responses are required to improve health during and after the COVID‐19 pandemic that: enable self‐determination; improve incomes, safety, food security and culturally‐safe healthcare; and address discrimination and trauma.